"Point Men": How religious women soldiers may restore Israel's "Citizens' Army". Issue 4 (2nd October 2017) - Feldman, Jan
ABSTRACT: It can be said that "a religious woman who decides to enlist in the IDF finds herself in two minorities: a woman in what is viewed as a man's world and a religious person in a secular environment." The recent phenomenon of women, particularly religious women, enlisting in the IDF has become a focal point among contending forces in Israel. Their presence in the IDF raises issues that go straight to the place where the military, civil society, religion, and state intersect. They are "point men" in a looming crisis over whether Israel will continue to field a military congruent with the founding model of a "people's army" infused with a unitary set of nationally accepted norms, or whether it will become the prize in a competition among identity groups intent on recreating the IDF in accordance with their particular set of values. Religious women soldiers stand to play a far more significant role in settling these questions than their small number might suggest. The trend they have set in motion may have a transformative impact on society by recalibrating the balance of power between religious authority and the state. The IDF's new and enthusiastic pool of recruits is defying religious edicts when they enlist. They could go on to foment a wider revolution in religious society long after their military service is completed. Finally, the cutting edge of feminism in Israel is arguably constituted by Orthodox women.